Multi-process driven unusually large equatorial perturbation electric fields during the April 2023 geomagnetic storm - Fejer, Bela G.; Laranja, Sophia R.; Condor, Percy (Frontiers in Astronomy and Space Sciences, 2024)
The low latitude ionosphere and thermosphere are strongly disturbed during and shortly after geomagnetic storms. We use novel Jicamarca radar measurements, ACE satellite solar wind, and SuperMAG geomagnetic field observations to study the electrodynamic response of the equatorial ionosphere to the 23-24 April 2023 geomagnetic storm. Our data show, for the first time, unusually large equatorial vertical and zonal plasma drift (zonal and meridional electric field) perturbations driven simultaneously by multi storm-time electric field mechanisms during both the storm main and recovery phases. These include undershielding and overshielding prompt penetration electric fields driven by solar wind electric fields and dynamic pressure changes, substorms, as well as disturbance dynamo electric fields, which are not well reproduced by current empirical models. Our nighttime measurements, over an extended period of large and slowly decreasing southward IMF Bz, show very large, substorm driven, vertical and zonal drift fluctuations superposed on large undershield driven upward and westward drifts up to about 01 LT. The nighttime radar data also show the occurrence of equatorial spread F irregularities with very strong spatial and temporal structuring. We compare our unusual vertical disturbance drifts with corresponding predictions from empirical prompt penetration and disturbance dynamo drift models. We also compare our data with results from previous experimental and modeling studies of equatorial storm-time electrodynamics.